Mission-Oriented Innovation Policy on the Example of Germany - Denis E. Bukshnaitis; Vera A. Zubenko; Andrey V. Frolov (Современная Европа, 2024)
New trends in global economic development, such as the processes of transnationalisation, economic and energy crises, gaps in foreign trade and logistics chains, challenges of modern technological development, intensify the competition of companies in world markets. The governments of the developed countries and large multinational corporations are actively engaged in radical transformation of the modern social and economic world development model on the basis of the 2030 Agenda for Sustainable Development. Germany is at the forefront of this global agenda. According to the German government, the development and introduction of transformative innovations is one of the tools that brings the world closer to sustainable development model. Such innovations do not only lead to technical progress, but also solve important social problems. To force through rapid modernisation German government has chosen a time-tested method – mission-oriented innovation policy (MOIP). State becomes the leading actor of the national innovation system, setting the goals of technological development and mobilising economic resources required to achieve these goals. For the first time, the missions of innovation policy were formalised in government documents in 2018. In early 2023 the new German government updated the drafting and composition of the missions. This article discusses the theoretical foundations of the MOIP approach to the formation of government innovation policy, describes the missions of the innovation policy of Germany, approved in 2018 and 2023, and examines the practical results of the implementation of some missions in 2018‒2022 on the example of renewable energy technologies introduction, building up battery cell production in Germany, developing clean mobility, putting German indigenous artificial intelligence technologies into practical application, digital healthcare, creating sustainable circular economies.